Response of various growth regulators and shade intensity to the growth of arabica coffee seedlings of Sigarar Utang variety - REVANDY ISKANDAR MUDA DAMANIK; CHAIRANI HANUM; LOKO JEREMIA SEMBIRING (Nusantara Bioscience, 2023)
Abstract. Damanik RIM, Hanum C, Sembiring LJ. 2023. Response of various growth regulators and shade intensity to the growth of arabica coffee seedlings of Sigarar Utang variety. Nusantara Bioscience 15: 85-89. The productivity of Arabica coffee (Coffea arabica L.) of the Sigarar Utang variety in Indonesia is still relatively low, especially in Simalungun District, North Sumatra Province, Indonesia. Growth regulators and shade are some factors that must be considered in nurseries. This research aims to determine the best growth regulators type and shade intensity for Arabika coffee seedling growth. The experiment was conducted from March to June 2022 in Nagori Ujung Bawang, Simalungun District, and the Central Laboratory of Agriculture Faculty, Universitas Sumatera Utara, Medan, North Sumatra. The study used a Split Plot design of 2 factors and 3 replications. The first factor (main plot) consists of 4 levels, namely 0, 50, 70, and 90% shade intensity. The second factor (sub-plot) consists of the three growth regulator treatments, i.e., auxin, cytokinin, and the combination of auxin and cytokinin. The results showed that the interaction between shade intensity and growth regulators had a significantly different effect on increasing root length. The shade treatment significantly affected plant height, leaf area, and total chlorophyll content of leaves. However, it did not affect the stem diameter. A shade intensity of 90% significantly increased plant height, leaf area, and total chlorophyll content of leaves.